Improving Mathematics Learning Outcomes On The Materials Of Lcm And Gcf In Students Of SDN 3 Sidorahayu, Wagir District, Malang Regency Through The Realistic Mathematic Education (RME) Model - Chumaidah, Kholisatun; Kumala, Farida Nur; Yasa, Arnelia Dwi (JUPE : Jurnal Pendidikan Mandala, 2025)
Mathematics learning in elementary school emphasizes providing direct learning experiences through the use and development of contextual process skills, meaning involving students directly in solving learning problems and connecting subject matter with everyday life. Based on the results of observations conducted in class V of SDN 3 Sidorahayu, Wagir District, Malang Regency during Mathematics learning, it was found that student learning outcomes were less than satisfactory, namely from 25 students only 10 students whose scores could reach KKM or ≥ 75, while 15 other students were still unable to reach KKM or ≤ 74.The purpose of this Classroom Action Research is to determine the impact of the use of the Realistic Mathematic Education (RME) learning model on the quality of the learning process and outcomes. This study uses a type of classroom action research (action research). The subjects of the study were fifth grade students. In this study, the researcher as a teacher (teacher), the fifth grade teacher (research partner) as an observer of the learning process of KPK and FPB. The results of the study indicate that the application of Realistic Mathematic Education (RME) can improve the quality of the process and learning outcomes of students on the KPK and FPB material in fifth grade students Semester 1 of Sidorahayu Elementary School, Wagir District, Malang Regency has good success criteria. This is evidenced by an increase in student learning outcomes, namely the percentage in cycle I 68.75% and in cycle II 78.84%. The increase in learning outcomes is also balanced by the creative development of students in cycle I 70.83% to 87.49% in cycle II. <w:LsdException Locked="false" Priority